Development of Learning Tools with the Means Ends Analysis Learning Model Based on Problem Solving in Newton's Law - Putri, Mila Rahmiza; Nasir, Muhammad; Ma'aruf, Zuhdi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This study aims to produce a learning tool with the Means Ends Analysis (MEA) learning model based on problem solving in Newton's Law material for class X high school students. This research was conducted to improve problem solving abilities among students who were still low, especially on Newton material and the lack of learning tools used. The learning tools developed in this study consist of Learning Implementation Plans (RPP), Student work sheets (LKPD), and Assesment Instrument Tests. This type of research is Research and Development (R&D) with a 4D development model (Define, Design, Develop, and Disseminate). The research instruments used were lesson plans validation sheets, LKPD, and Cognitive Learning Outcomes Tests used by validators to assess learning tools. Data analysis in this study used descriptive analysis, by calculating the validity score of each learning device indicator. Based on the results of the validity analysis, the average value of lesson plan validity is 0.78. The average validity of LKPD is 0.75. The average validity of the Learning Outcomes Test Instrument is 0.802. The average validity of the overall device is 0.77, the learning tool for the MEA model based on problem solving in Newton's Law material is declared valid and suitable for use as a learning tool in Newton's Law material.Keywords: learning tools, MEA, problem solving, newton’s law